Dismembered and non-dismembered retroperitoneoscopic pyeloplasty for the treatment of ureteropelvic junction obstruction in children - Subotic, Svetozar; Weiss, Hagen; Wyler, Stephen; Rentsch, Cyrill A.; Rassweiler, Jens; Bachmann, Alexander; Teber, Dogu (World journal of urology, 2013)
Open dismembered pyeloplasty according to Anderson-Hynes (AHP) is the gold standard treatment for ureteropelvic junction obstruction in children. However, during the last decade, the management has been revolutionized with introduction of laparoscopy and endourology yielding comparable results and less morbid outcomes.
Published online: 22 May 2012
Gesehen am 22.03.2022